Bilateral Absence of the Superior Vena Cava. (2nd October 2012) - Ylänen, Kaisa; Poutanen, Tuija; Savikurki-Heikkilä, Päivi; Uotila, Jukka; Korppi, Matti; Eerola, Anneli
Abstract : Bilateral absence of the superior vena cava (SVC) is a very rarely detected, mainly asymptomatic congenital vascular anomaly. Though usually innocent, this anomaly may complicate cardiothoracic surgery and certain procedures like central venous catheter insertion. This SVC anomaly is poorly known, and we assume that its incidence in the general population may be higher than detected. In this paper, we summarize current knowledge on this anomaly and its clinical implications. In addition, we present a neonatal case with bilateral absence of the SVC associated with a fetal cystic hygroma. Conclusion . Totally absent SVC can cause unexpected problems during cardiothoracic surgery. Suspicion of SVC absence should arise in basic echocardiography. Our paper suggests that, like other congenital anomalies, bilateral absent SVC may be associated with a fetal cyctic hygroma.